Application of reliability, availability and maintainability analysis to dynamic positioning systems used in offshore operations. - Clavijo Mesa, Maria Valentina (2019)
Nowadays, Dynamically Positioned (DP) units are responsible for most of offshore oil exploitation operations, including drilling and maintenance campaigns. Due to the larger congestion of the oil fields, keep the vessel position, despite the environmental forces, is a critical issue. This study aims to propose a methodology and apply it for a RAM analysis (Reliability, Availability & Maintainability) of DP System of two different generations (DP class 2 and DP class 3) in order to obtain accurate information that allows subsequently define their restriction diagrams. The DP system, including various subsystems, DP classes and applications, are introduced and discussed. In addition, the necessary concept and techniques to analyze the Reliability, Availability and Maintainability of DP system are explained. In the reliability analysis, two interest events (free drift and controlled drift) are evaluated for different operation times (12, 9, 6 and 3 months); and, as expected, the DP3 system is more reliable than DP2 system in all scenarios. Regarding maintainability, the Monte Carlo Simulation exposed that in more than 90% of the free drift, the maintenance teams of the DP systems under study are able to recover the positioning of the units in the first 6 hours; while the recovery times lower than 3 hours, represent 43% of simulated free drifts. The asymptotic availability analysis of DP2 and DP3 systems shows availability greater than 0.9998 even for operational times greater than 15 years. The study concludes with an evaluation of the impact of the uncertainty in the failure rates of critical components of DP systems and the use of a non-parametric method for the design of probability density function of repair times. Finally, it is suggested that future studies take into consideration the impact of human factors in the DP system RAM analysis.